Sosialisasi Inovatif Pembelajaran Geografi Berbasis Deep Learning untuk Meningkatkan Minat dan Pemahaman Siswa - Lasaiba, Mohammad Amin; Asep, Asep; Ansiska, Paisal; Halatu, Yosepus Anthony; Manakane, Susan Evelin; Pinoa, Herwic (Universitas Pattimura, 2025)
The development of artificial intelligence technology, particularly deep learning, provides significant opportunities to enhance the effectiveness of Geography learning. This socialization activity was conducted at SMA Negeri 3 Ambon City to equip teachers with the ability to integrate deep learning into the learning process to make it more engaging and adaptive to students’ needs. The method used was a participatory approach through theoretical sessions, practical application, interactive discussions, and questionnaire-based evaluation. Results showed that 88% of participants displayed high enthusiasm, 85% improved their understanding, and 78% felt ready to apply the technology in teaching. The activity demonstrated that practice-based training effectively enhances teachers’ competence in the digital era. It implies that such programs should be promoted as models for strengthening teacher professionalism through the integration of modern learning technologies in secondary education.